The Lazarki Procession in Inyevo, Radoviš: Ritual and Tradition in North Macedonia - Tamayo, Jose Antonio Lorenzo; Madili, Meryem (Ethnographica et Folkloristica Carpathica, 2025)
Lazarus Day is an important springtime tradition among Orthodox Christians in the Balkans. In the Republic of North Macedonia, many villages mark the occasion with a ritual conducted by female performers, the lazarki. Traditionally, the lazarki visit each home in the village to bless family members by singing unique songs. This ethnographic work intends to explore and document the tradition in Inyevo, a lowland and upland community in the Municipality of Radovis. Compared to other villages in Macedonia, the lazarki in Inyevo perform two connected rituals conducted eight days before Palm Sunday. On a Saturday, the lazarki perform the willow picking and willow offering in the monasteries, while the traditional home visitations happen on a Sunday. In exploring and documenting the tradition, fieldwork was conducted between 27 and 28 April 2024. The fieldwork included interviews (i.e., with the performers, a local family, people in the village) and observation of the rituals performed by the lazarki. The Lazarki in Inyevo exemplifies a tradition evoking themes on gender, the contemporary role of women in rituals, and as a form of authentic expression of faith.